Hubungan Penggunaan Sosial Media Instagram Dengan Kerentanan Korban Cyber Harassment - Sobri; Noor , Febriyan (SISI LAIN REALITA, 2021)
Cyber ​​harrasment is the result of improper use of the internet and it is a verbal crime where most of the victims are children and adolescents. This crime need internet as a media to do these acts. The aim of this research was to determine the relationship between the use of social media Instagram and the vulnerability of of cyber harrasment victims. The research uses quantitative methods, with correlational approach. The research analyzed the behaviour of the Instagram users at @anaksekolahpku account. The result of this research showed that that there the teenagers who made an Instagram become part of their lives. They even deliberately include their personal identities and daily activities for public consumption. This is related to the result of the research about the vulnerability of victims of cyber harassment, where teenagers even get / provide some comments, vulgar videos, personal messages, etc., which lead to cyber harassment. So, it can be concluded that there was significant relationship between the use of social media Instagram and the vulnerability of of cyber harrasment victims.